Evolution of Commercial Facilities in New Urban Areas of Hanoi: Potential of Sustainable Neighborhood-level Third Place Making - Tran, Minh Tung; Chu, Ngoc Huyen; Phan, Tien Hau (International Journal of Sustainable Construction Engineering and Technology, 2021)
Shopping contributes largely to how people feel part of and enjoy KDTMs (Khu Do Thi Moi - new urban areas) - the carefully planned new sites, well provided with infrastructure, and very attractive of Hanoi in the market economy. Among the three facilities that are rated as most important by KDTM’s residents - education, health care, and shopping, the third is considered a pure civil space. This space clearly reflects the changes of politico-economic context and decision-making actors. Participation of the private sector in the newly formed market economy after a long period under State-run subvention and the consumerism entailed various ways to develop neighborhood-level commercial facilities. This paper aims to analyze and discuss on: firstly, the neighborhood-level commercial facilities have ‘promptly’ updated the changes in Vietnam's political-economic; secondly, the classify of KDTMs has resulted in a corresponding differentiation of commercial facilities according to the will of the project owners and the target consumer-resident; finally, facing the global ‘death’ of shopping malls, the KDTMs malls are trying to find themselves a new ‘vitality’: they are being ‘publicized’ to (re)create the third places in KDTM, that encourage social interaction in the limited spaces - intersperse public and private practices.